Relationship between diabetic retinopathy and cognitive impairment in patients with type 2 diabetes mellitus (Ukrainian Journal of Ophthalmology, 2026)
Background. Retinal microcirculation disorders can be diagnosed at the early stage of complication development while cerebral circulation disorders and cognitive impairment are diagnosed at a rather late stage, when structural changes develop in the brain of the patients. Most authors have investigated the cognitive function by studying memory, information and operation processing speed not taking into consideration the sensitivity of tests in this group of patients.  The relationship between diabetic retinopathy and cognitive impairments has not investigated.The purpose of the present study was to investigate the state of cognitive function in type 2 diabetes patients with diabetic retinopathy and to determine the most sensitive cognitive tests.Material and Methods. The study included 93 patients with type 2 diabetes, aged 50 to 80. The patients were divided into two groups: DR-group and non-DR group. Cognitive function was studied using tests as follow: a “five words” test, Mini-mental State Examination (MMSE); Frontal Assessment Battery (FAB), a clock drawing test, a “fifteen words” test, the Brixton test, the Trail making test (TMT), Digit span forward and backforward (DSFB), the Verbal fluency test, the Тest symbol and the Stroop color test.Results. The TMT test showed significantly better performance in regard of working memory, memory flexibility, and executive functions in the group of patients without DR as compared to those with retinopathy. Statistically significant impairment of the executive function in patients with DR was confirmed by the Brixton test in comparison with that parameter in non-DR-group. According to the TMT and the Brixton test, patients without DR had better performance of working memory and memory flexibility as well as executive functioning compared to DR patients, which indicates lesions of frontal and prefrontal areas of the brain in those patients with DR. The Brixton test seems to be more sensitive and easy to use for screening the cognitive impairments in patients with diabetes mellitus and DR.
Keywords: diabetes mellitus; mild cognitive impairment; dementia; diabetic retinopathy